An approach to Pspice-aided control loop design of DC-DC converter systems - Muhamad, Nik Din; Shafie, Abd Jaafar (2003)

(untitled)
A new approach to using Pspice is designing feedback for DC-DC converter systems is introduced in this paper. In this new approach, the feedback design procedures are programmed and made as a subcircuit in Pspice. For this purpose, an option available in PSpice called Analog Behavioral Modeling (ABM) is used. By using the subcircuit, the component values of the errror amplifier can be easily obtained by means of Pspice DC analysis. The methodology of development is presented in detail. Application examples are included to demonstrate the effectiveness of the proposed approach in designing feedbacks for DC-DC converters